Stakeholders' hopes and concerns about the COVID-19 vaccines in Southeastern Nigeria: a qualitative study - Uchechukwu Madukaku Chukwuocha; Chiagoziem Ogazirilem Emerole; Greg Ndubeze Iwuoha; Ugonma Winnie Dozie; Princewill Ugochukwu Njoku; Chidinma Onyebuchi Akanazu; Precious Okechukwu Eteike; Charlotte Hemingway (BMC, 2022)
Abstract Background Equitable access and high uptake of safe and effective vaccines is critical to ending the COVID-19 pandemic. To ensure the success of these vaccines, particularly in many developing and under-developed parts of the world, the concerns of local communities including fears, potency, and levels of acceptance should be addressed. This study assessed community stakeholders' perceptions in parts of Southeastern Nigeria about COVID-19 vaccine, towards engaging them effectively to ensure the success of the vaccination campaigns. Methods A qualitative study was conducted involving fourteen stakeholders from the Southeastern geo-political zone of Nigeria selected using purposive sampling. In-depth semi-structured individual interviews lasting about 30 min were used to collect data. Data analysis was informed by a general inductive approach. Results Stakeholders hoped that the development and roll out of the vaccines will bring COVID -19 to an end, will help to maintain good health and allow people get back to normal life. On the other hand, stakeholders expressed their concerns and worries about the "speed" with which the vaccines are being produced, possibility of future adverse effects from vaccination, misinformation, and level of preparedness in the health system to implement the vaccine campaign. Conclusions This study identified that more needs to be done to improve perceptions of those who influence health decisions in communities towards COVID-19 vaccines. This includes firstly, the involvement of the community and religious leaders in vaccine promotion. Secondly, it is imperative to develop and disseminate persuasive messaging on vaccine effectiveness and safety targeted at both health professionals, policymakers, and the community which are culturally sensitive and address identified concerns among health workers. Thirdly, the health systems should be strengthened and system-level interventions that directly target one or more of the WHO's six health system building blocks: service delivery, health workforce, health information systems, access to essential medicines, financing, and leadership/governance.